SISTEM INFORMASI UKM BERBASIS WEBSITE PADA DESA SUMBER JAYA - Jonathan, William; Lestari, Sri (IBI Darmajaya, 2015)
IBI Darmajaya as institutions engaged in the field of education it should perform community service activities as a form of discordant to the public anyway. One location for community service activities is Sumber Jaya. In the village of Sumber Jaya livelihoods of the majority are farmers, but there are some efforts made public in the form of small and medium enterprises (SMEs) such as SMEs chips, Mushroom, Springbed, Tempe and others. These SMEs will need to be preserved and developed to become the economic strength of the local community, so there needs to be a touch of technology to publicize its existence as a medium for the promotion of SMEs. On that ground, he built a web-based information media so expect every existing SMEs in Sumber Jaya can be widely known. Keywords: website, SME